Friendship with God : an uncommon dialogue - Walsch, Neale Donald (New York : G.P. Putnam's Sons, 1999)
The sequel to the "Conversations with God" trilogy explores the various ways in which the wisdom and insights of "Conversations with God" can be applied to everyday life and explains what we have to do to develop a working friendship with God
Keywords: Spiritual life -- Miscellanea; God -- Miscellanea; Friendship -- Religious aspects -- Miscellanea